The Repressed Keynes - Gustav A. Horn (Wirtschaftsdienst)
Abstract This month marks the 75th anniversary of the death of John Maynard Keynes. He was one of the most important economists of the 20th century, if not of any century. Yet his teachings and advice were already highly controversial during his lifetime. This applied even more after his death. Keynesian ideas dominated economic policy in the postwar period. But since the 1970s at the latest, their intellectual appeal began to wane noticeably in the face of concurrently rising unemployment, national debt and inflation. Recently, however, a trend reversal has become apparent, which is related to mistakes in economic policy as well as to new challenges.